2014
DOI: 10.1016/j.cej.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of manganese oxide as adsorption sites for hydrogen sulfide on granulated coal ash

Abstract: It is important to remove hydrogen sulfide to maintain healthy ecosystems as well as viable aquaculture activities in enclosed water bodies. Granulated coal ash with high adsorption capacity for hydrogen sulfide is a by-product generated from coal combustion processes in coal-fired power plants. The purposes of this study were to (1) verify the regeneration of the adsorption sites for hydrogen sulfide on the granulated coal ash by redox reaction which changes between oxic and anoxic conditions and (2) prove th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…XANES is a convenient method to analyze the species of 3d-elements in crystalline, as well as amorphous materials. Asaoka et al determined the oxidation state of Mn in granulated coal ash via XANES [10], while Kim et al used XANES for Mn speciation in steel-making slags [11]. In general, the oxidation state, the coordination sphere, and in some cases the actual compound can be determined.…”
Section: Speciation Of Oxidation States In Spinel Systemsmentioning
confidence: 99%
“…XANES is a convenient method to analyze the species of 3d-elements in crystalline, as well as amorphous materials. Asaoka et al determined the oxidation state of Mn in granulated coal ash via XANES [10], while Kim et al used XANES for Mn speciation in steel-making slags [11]. In general, the oxidation state, the coordination sphere, and in some cases the actual compound can be determined.…”
Section: Speciation Of Oxidation States In Spinel Systemsmentioning
confidence: 99%
“…Even though demonstrating fast sulfide removal rates at first, the treatment performance gradually decreases as Mn becomes depleted due to its interaction with sulfide [37]. In our previous study, we demonstrated that application of low anodic potentials enabled continuous regeneration of the MnxOy catalyst coating, thus preventing its gradual depletion [38].…”
Section: Introductionmentioning
confidence: 92%
“…A costeffective adsorbent for removing H 2 S gas was developed in this study by mixing coal fly ash, which is a by-product of coal electric power plants and blast furnace cement, to increase the specific surface area through pozzolanic reaction. A coal fly ash-blast furnace cement composite was previously reported to be capable of removing H 2 S from both fresh and seawater (Asaoka et al 2012;Asaoka et al 2014;Asaoka et al 2017). However, no data on the removal of H 2 S gas by the coal fly ash-blast furnace cement composite are available.…”
Section: Introductionmentioning
confidence: 99%